Paradoxes de l’intimité dans la littérature matrimoniale (XVIe siècle) - Cécile Codet (E-Spania)
The Institutione foeminae christianae by Vives (1524), the « Letra para Mosén Puche » by Guevara (1524) and the Coloquios matrimoniales by Luján (1550) all tackle how husband and wife get married and how they live together, including descriptions of the more intimate aspects of their lives. But what kind of intimacy are they dealing with? Giving the fact that the life described in these texts is, most of the time, purely theoretical and exemplary, it seems that they fail in having access to what intimate life really is, given it is personal and individual. Nevertheless, these texts tell something about intimacy, which they consider as the heart of the marital relation. Moreover, to these authors, intimacy is not just something to write about. Used as a pedagogical strategy, their display of intimacy becomes a means to get into the readers’ lives and more specifically into their most private aspects.